Energy Efficiency Optimization in Cooperative Spectrum Sensing by NOMA - Awasthi, Meenakshi; Nigam, J.Madhav; Kumar, Vijay (International Journal of Engineering and Technology, 2018)
Energy efficiency improvement is a major point of concern in cooperative scenario of cognitive radio networks, so as to compensate the overhead occurred due to power consumed by multiple numbers of secondary users. Non-orthogonal multiple access (NOMA) is a potential technique to get the higher spectrum efficiency for 5G systems. The basic feature of NOMA is to utilize the same channel, time and code but at different power levels, which results in higher spectrum efficiency (SE). In this article, firstly the cognitive radio (CR) inspired NOMA is generalized by multiple primary users. Then, energy efficiency (EE) is optimized for the proposed system. An efficient algorithm is proposed for the non-convex fractional programming problem. Simulation results show the superior performance over conventional multiple accesstechniques.Â Â